Penerapan Teknologi Odoo Dalam Prespektif Perubahan Sosial pada Layanan Kesehatan - Lulu Jola Uktolseja; Melda Agnes Manuhutu; Natasya Virginia Leuwol; Gilber Gilber; Yohana Yohana; Alfa Alfa; Apriando Apriando; Andianus Andianus; Abraham Manuhutu (Universitas 45 Surabaya, 2025)
The rapid development of information technology has driven significant social changes in various sectors of life, including the health service sector and Micro, Small, and Medium Enterprises (MSMEs). One concrete example is the Miftah Pharmacy in Sorong City, Southwest Papua, which is an MSME in the pharmaceutical and health service sectors. Before technological intervention, this pharmacy still used a manual system in recording transactions, managing drug stocks, and financial reporting. This condition causes delays in the delivery of information, low data accuracy, and decreased service quality to the community. Responding to social dynamics and challenges in the digital era, this service program aims to analyze and implement a website-based information system using the Odoo platform as a service digitization solution. The methods used include observation, interviews, training, and technical assistance to pharmacy managers. The results of the implementation of the system show an increase in work efficiency, accuracy in the preparation of financial statements, and acceleration of service to customers. In addition to technical benefits, this implementation also reflects the form of social adaptation of MSMEs to the growing digital culture changes. This transformation is proof that digitalization not only touches the operational aspect, but also strengthens the social and managerial capacity of business actors in facing modern challenges. Thus, the findings of this program are expected to be a reference and inspiration for other MSME actors, especially in the eastern region of Indonesia, to integrate information technology into their business systems in a sustainable and adaptive manner to the times.